The Theory of Zariah Legal Movement and It's Application in Market Law in Indonesia - Mustapa Khamal Rokan (Ijtimā`iyya: Journal of Muslim Society Research, 2020)
This paper explains the legal movement zariah legal theory of history, concepts, philosophies, ways of working and its implementation in developing legal issues. The legal issue taken is the issue of antitrust law in Indonesia, especially in the contestation of modern markets and traditional markets in Indonesia. This paper uses a qualitative method with secondary data retrieval which is analyzed with a normative approach, history and legislation. The results showed the law must be able to move (movement) to form the ideal law. In the ideal market law that is by protecting (sadd), empowering (fath) and also collaborating (jam'u). The form of protection (sadd), a small market can be done in accordance with the conditions and situations that develop in the market. The form of legal protection can be in the form of legal protection of existence, giving tax payment incentives, protection against price competition, protection through granting location and time permits, protection by differentiating types of products in each type of market, as well as cooperating between modern markets and markets traditional.